A novel superfamily of transporters for allantoin and other oxo derivatives of nitrogen heterocyclic compounds in Arabidopsis - Desimone, Marcelo; Catoni, Elisabetta; Ludewig, Uwe; Hilpert, Melanie; Schneider, Anja; Kunze, Reinhard; Tegeder, Mechthild; Frommer, Wolf Bernd; Schumacher, Karin (The plant cell, 2002)
A wide spectrum of soil heterocyclic nitrogen compounds are potential nutrients for plants. Here, it is shown that Arabidopsis plants are able to use allantoin as sole nitrogen source. By functional complementation of a yeast mutant defective in allantoin uptake, an Arabidopsis transporter, AtUPS1 (Arabidopsis thaliana ureide permease 1), was identified. AtUPS1 belongs to a novel superfamily of plant membrane proteins with five open reading frames in Arabidopsis (identity, 64 to 82%). UPS proteins have 10 putative transmembrane domains with a large cytosolic central domain containing a “Walker A” motif. Transport of 14C-labeled allantoin by AtUPS1 in yeast exhibited saturation kinetics (K m ∼ 52 μM), was dependent on Glc and a proton gradient, and was stimulated by acidic pH. AtUPS1 transports uric acid and xanthine, besides allantoin, but not adenine. Protons are cosubstrates in allantoin transport by AtUPS1, as demonstrated by expression in Xenopus laevis oocytes. In plants, AtUPS1 gene expression was dependent on the nitrogen source. Therefore, AtUPS1 presumably is involved in the uptake of allantoin and other purine degradation products when primary sources are limiting.